Ambient viral and bacterial distribution during long-range transport in Northern Taiwan. (1st February 2021) - Chen, Nai-Tzu; Cheong, Ngok-Song; Lin, Chuan-Yao; Tseng, Chun-Chieh; Su, Huey-Jen
Abstract: Long-range transport (LRT) reportedly carries air pollutants and microorganisms to downwind areas. LRT can be of various types, such as dust storm (DS) and frontal pollution (FP); however, studies comparing their effects on bioaerosols are lacking. This study evaluated the effect of LRT on viral and bacterial concentrations in Northern Taiwan. When LRT occurred and possibly affected Taiwan from August 2013 to April 2014, air samples (before, during, and after LRT) were collected in Cape Fugui (CF, Taiwan's northernmost point) and National Taiwan University (NTU). Reverse-transcription quantitative polymerase chain reaction (RT-qPCR) was applied to quantify influenza A virus. qPCR and qPCR coupled with propidium monoazide were, respectively, used to quantify total and viable bacteria. Types and occurrence of LRT were confirmed according to the changing patterns of meteorological factors and air pollution, air mass sources (HYSPLIT model), and satellite images. Two Asian DS and three FP cases were included in this study. Influenza A virus was detected only on days before and during FP occurred on January 3–5, 2014, with concentrations of 0.87 and 10.19 copies/m 3, respectively. For bacteria, the increase in concentrations of total and viable cells during Asian DSs (17–19 and 25–29 November 2013) was found at CF only (from 3.13 to 3.40 and from 2.62 to 2.85 log copies/m 3, respectively). However, bacterial levels at NTU and CF both increased during FP and lasted for 2 days after FP. In conclusion, LRT increased the levels of influenza A virus and bacteria in the ambient air of Northern Taiwan, particularly at CF. During and 2 days (at least) after LRT, people should avoid outdoor activities, especially in case of FP. Graphical abstract: Image 1 Highlights: Bioaerosols were monitored before, during, and after long-range transport. Dust storm and frontal pollution cases transported bacteria and influenza A virus. Both non-viable (dominant) and viable bacteria were transported. The effect of long-range transport was lasted to at least two days after events. Factors associated bacterial levels were varied between background and event days. Abstract : A capsule of no more than two lines that summarizes the main finding: Asian DS and FP both can transport virus and total and viable bacteria to the downwind area, which can last up to at least 2 days after LRT.